Characterisation of multi-element (Nb, Cr) N thin films deposited by unbalanced magnetron sputtering - Tan, Jen Ngee. (2008)
Tool steels have long been used to manufacture tools for high speed cutting and machining due to its excellent strength, toughness, and heat resistance. However, though the excellent mechanical properties, the tool surface and near surface regions are subjected to the most destructive forces, for example, wear, high stresses, elevated temperatures, and corrosive environments.